Research on the Influence of Engineered Cementitious Composite’s Water–Cement Ratio and Fiber Content on the Mechanical Performance of Foam Lightweight Soil - Qingguo Yang; Yu Zhou; Ya Li; Kelin Chen; Wujing Yin; Yunhao Li (Buildings)
This study explores the influence of the water–cement ratio and fiber content in engineered cementitious composite (ECC) on the mechanical characteristics of foamed lightweight soil (FLS) through experimental analysis. Two types of cementitious materials—ECC and ordinary Portland cement (OPC)—were utilized to create FLS specimens under identical parameters to examine their mechanical performance. Results indicate that ECC-FLS exhibits superior toughness, plasticity, and ductility compared to OPC-FLS, validating the potential of ECC as a high-performance material for FLS. To assess the influence of the ECC water–cement ratio, specimens were constructed with varying ratios at 0.2, 0.25, and 0.3, while maintaining other parameters as constant. The experimental results indicate that as the water–cement ratio of ECC increases, the flexural strength, compressive strength, flexural toughness, and compressive elastic modulus of the lightweight ECC-FLS gradually increase, exhibiting a better mechanical performance. Moreover, this study investigates the effect of basalt fiber content in ECC on the mechanical properties of FLS. While keeping other parameters constant, the volume content of basalt fibers varied at 0.1%, 0.3%, and 0.5%, respectively. The experimental results demonstrate that within the range of 0 to 0.5%, the mechanical properties of FLS improved with increasing fiber content. The fibers in ECC effectively enhanced the strength of FLS. In conclusion, the adoption of ECC and appropriate fiber content can significantly optimize the mechanical performance of FLS, endowing it with broader application prospects in engineering practices. ECC-FLS, characterized by excellent ductility and crack resistance, demonstrates versatile engineering applications. It is particularly suitable for soft soil foundations or regions prone to frequent geological activities, where it enhances the seismic resilience of subgrade structures. This material also serves as an ideal construction solution for underground utility tunnels, as well as for the repair and reconstruction of pavement and bridge decks. Notably, ECC-FLS enables the resource utilization of industrial solid wastes such as fly ash and slag, thereby contributing to carbon emission reduction and the realization of a circular economy. These attributes collectively position HDFLS as a sustainable and high-performance construction material with significant potential for promoting environmentally friendly infrastructure development.